HEDONISME DUNIA NYATA DAN MEDIA SOSIAL DALAM PERSPEKTIF DRAMATURGI ERVING GOFFMAN (Kualitatif Pada Mahasiswa Pendidikan Ekonomi Angkatan 2020) - Ricka Holiah; Rendra Gumilar; Ai Nur Solihat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the phenomenon of hedonism lifestyle among students and indicated the occurrence of dramaturgy addressed through their real world and social media. This refers to activities carried out to achieve a pleasure and direct satisfaction both in terms of physical and emotional. The purpose of this study is to find out what dramaturgy is done by students to achieve this satisfaction and form the desired self-image so that it can be validated by others. The method in this study uses descriptive qualitative with data collection techniques through observation, interviews and documentation with triangulation data validity techniques, as well as purposive sampling analysis techniques. The research sample was three informants of economics education students class of 2020 who worked part-time, freelance and did not work. The results of the study found several facts that in real life and social media the three informants tended to carry out almost the same dramaturgical activities with different satisfaction goals so that it was easier to pour into social identity theory.